Perinatal mental health research in Malaysia: where are we? - Mohd Arifin, Siti Roshaidai (2023)
The perinatal period is well-known period of extreme change either physically or emotionally for some women. The changes could make them at high risk of developing mental health disorders. Perinatal mental disorders may contribute to negative consequences such as low quality of life, poor maternal-infant bonding, suicide and infanticide. This plenary talk discuss about the main issues related to perinatal mental health in Malaysia, its current management and challenges and plan for the future improvement for the maternal health and wellbeing in Malaysia.